Problematic issues of spacecraft development for contactless removal of space debris by ion beam. (April 2021) - Obukhov, V.A.; Kirillov, V.A.; Petukhov, V.G.; Popov, G.A.; Svotina, V.V.; Testoyedov, N.A.; Usovik, I.V.
Abstract: Application of the method of removal of space debris objects by an ion beam - the IBS method - seems to be the most effective for cleaning the GEO region. This is due to the low energy consumption for transfer one object in a safe orbit delta-V≃11 m/s and the possibility of removal several objects by one spacecraft. The service spacecraft for this purpose can be developed on the basis of telsat technology, taking into account its functions. Such a spacecraft should contain an ion beam injector to act on the removed object and an electric propulsion system, which serves to compensate for the ion injector thrust and to control the spacecraft motion both during transportation of the removed object and during interorbital flights. The development of a weakly diverging ion beam injector, determination of the composition and structure of an electric propulsion system, ballistics of the optimal sequence of interorbital flights, and development of an algorithm for controlling a virtual cluster: spacecraft-removed object are discussed in the article. In the majority of works on IBS, commercial ion thrusters are considered as an ion injector and engines. However, ion beams from ion thrusters have a half angle of divergence of 12 0 -15 0 . When propagating in outer space, the ion beam expands irresistibly due to electron thermal effects. As a result, the distance at which the spacecraft must follow the removed object during its transportation for effective impulse transmission to it should be small (estimated, about 7 m). Taking into account the dimensions of both objects and the uncontrolled movement of the removed object relative to its center of mass, the object transportation operation carries noticeable risks. The results of an experimental study of a prototype of an ion injector with an initial half angle of divergence of 2 0 -4 0 are presented. The use of such an injector would provide a distance between objects of 15–20 m and reduce the risk of their collision. In connection with IBS, various aspects of spacecraft control during transportation of an object with one, two or more engines as part of the electric propulsion system are considered. In the conceptual design of the spacecraft presented in this work, the electric propulsion system contains two stationary plasma thrusters, each of which is mounted with the possibility of independent rotation respect to two mutually perpendicular directions. Spacecraft motion control, including thrust vector control, is carried out by means of the thrusters coordinated rotation. The characteristics of the spacecraft and its subsystems intended for the removal of several objects are conceptually considered. For example, parameters of the mission for the removal of up to 10 objects from the NORAD catalog from the GEO region are given. In the future, using the result obtained, the control of SC of this scheme when IBS implementing in the low-Earth orbit will be considered. Highlights: A spacecraft (SC) for space debris objects (SDO) removal use two electric propulsion thrusters mounted on two-axis gimbals. Experiments with an ion injector demonstrate a weakly diverging ion beam to be effective at a large distance between SC and SDO. For stable control of the SC-SDO cluster coordinated engine turns are used.